PENGARUH DISIPLIN KERJA DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PADA HYPERMART PEJATEN VILLAGE PASAR MINGGU DI JAKARTA SELATAN - Rahmi Hermawati; Andi Sopandi; Ratna Sari (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This research aims to determine the influence of work discipline and job promotion on employee performance, both partially and simultaneously. The research method used is quantitative, and the nature of the research is associative, with linear regression analysis. Based on the test results, it was found that work discipline has a positive and significant influence on employee performance, with a calculated t-value of 5.613 > tabled t-value of 1.983 and a significance value (sig) of 0.000 < 0.05. This indicates that the better the work discipline of employees in the company, the higher their performance. Job promotion also has a positive and significant influence on employee performance, with a calculated t-value of 4.672 > tabled t-value of 1.983 and a significance value (sig) of 0.000 < 0.05. This shows that the more frequent a company provides job promotions to employees, the higher their performance will be. Both work discipline and job promotion have a positive and significant influence on employee performance, with a calculated F-value of 53.952 > tabled F-value of 3.09 and a significance value (Sig) of 0.000 < 0.05. This indicates that if work discipline and job promotion can be improved and enhanced, employee performance will increase. The adjusted coefficient of determination (Adjusted R Square) is 0.505, indicating that the variables of work discipline and job promotion contribute 50.5% to employee performance, while the remaining 49.5% is influenced by other factors outside the scope of this study.